2011
DOI: 10.1149/1.3614529
|View full text |Cite
|
Sign up to set email alerts
|

Aging of a Commercial Graphite/LiFePO4 Cell

Abstract: The aging behavior of a commercial 2.3 Ah graphite/LFP cell during a year of cycling or storage at either 25 or 45 C is investigated. The performance decline of the cells during the aging period is monitored by non-destructive electrochemical techniques and is discussed in detail. An in-depth analysis of the aging results reveals that aging manifests itself more in terms of capacity loss rather than in terms of impedance increase, regardless of the cycling or storage conditions and of the temperature. The capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
193
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(207 citation statements)
references
References 34 publications
14
193
0
Order By: Relevance
“…Under this hypothesis, the charge consumed in the side reaction at the cathode corresponds to the reversible capacity loss (i.e., Q rev ) whereas that at the anode corresponds to total capacity loss (i.e., Q irr + Q rev ). Safari et al [37], based upon an analysis of the potential variations of graphite/LFP cells during OCP storage, demonstrated the contribution of both electrodes to the aging process under storage and that a minor lithium uptake due to side reaction at the charged LFP electrode partially compensates for the lithium release because of side reaction leading to SEI growth at the graphite electrode. In Fig.…”
Section: °Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this hypothesis, the charge consumed in the side reaction at the cathode corresponds to the reversible capacity loss (i.e., Q rev ) whereas that at the anode corresponds to total capacity loss (i.e., Q irr + Q rev ). Safari et al [37], based upon an analysis of the potential variations of graphite/LFP cells during OCP storage, demonstrated the contribution of both electrodes to the aging process under storage and that a minor lithium uptake due to side reaction at the charged LFP electrode partially compensates for the lithium release because of side reaction leading to SEI growth at the graphite electrode. In Fig.…”
Section: °Cmentioning
confidence: 99%
“…It is safe, because of a high thermal stability, and has a low toxicity and a low cost compared to cathodes such as LiCoO 2 . Several aging studies concerned with life performance of LFP-based cells are found in the literature [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests are known to be largely unrepresentative of the day to day battery operation within an EV. Research published by Barre et al [8] has indicated that complex electrical loading profiles result in different ageing characteristics than conventional galvanostatic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Many of these numerical studies are based on the mathematical models developed by Newman et al.…”
Section: Introductionmentioning
confidence: 99%